FAILE : works on wood : process, paintings & sculpture - FAILE (Artist collective); Gestalten Verlag (Berlin : Gestalten, 2014)
"Faile: Works on Wood is a new collection of essays and rich color photographs that showcases Faile's exploration of wood in their practice. It presents a broad swath of their projects from the past decade, from early work using salvaged material to more recent commissions, such as their towering installation at the New York City Ballet. The book features both critical writing and reflections by the artists on now iconic facets of their work in and out of the studio, including their interactive Puzzle Boxes, carved Prayer Wheels, and bold, large-scale painting."--The publisher.
Foreword: Bulk transmissions / Peter Doroshenko -- Introduction: Work on wood in contemporary art / Ian Bourland -- Inspiration: Storefront typography & quilts of Gee's Bend -- Street art & stencils on wood -- Hasta Pronto, Centre Cultural Es Jonquet, Mallorca, Spain -- Untitled, FIFTY24SF Gallery, San Francisco, California -- Apple Boxes -- From Brooklyn with Love, Lazarides Gallery, Greek Street, London, England -- Nothing Last Forever, Chrystie Street, Lazarides Gallery, New York, New York -- Prayer Wheels -- Lost in Glimmering Shadows, Lilian Baylis School, Lazarides Gallery, London, England -- Street Wheels, Brooklyn, New York -- Puzzle boxes -- Pallet paintings -- Bedtime Stories, Perry Rubenstein Gallery, New York, New York -- Fragments of FAILE, Lazarides Rathbone Gallery, London, England -- Works on wood 2011-2012 -- Essays -- Wrong God / Julia Langbein -- Shadow boxes / Meredith Ries -- Organic hackers / Nate Harrison -- Wild west-Dallas 2014 / Pedro Alonzo -- Installations -- Les Ballets de FAILE, NYC Ballet, Lincoln Center, New York, New York -- Where Wild Won't Break, Dallas Contemporary, Dallas, Texas -- Works on Wood 2012-2013.
Keywords: FAILE (Artist collective); Painting, American -- 21st century; Wood sculpture, American -- 21st century; Wood in art